Islamic Relief Project: Restoring Sustainable Livelihoods Through Islamic Social Enterprise - Muhammad Fadil Alwi; Elimawaty Rombe; Maskuri Sutomo; Rian Risendy (Journal of Humanities, Community Service, and Empowerment, 2025)
Post-disaster economic recovery is a complex challenge, requiring a sustainable approach to rebuilding a resilient economic foundation. This study explores the role of the Islamic Relief Project in facilitating post-disaster sustainable livelihood recovery in the Petobo area, Central Sulawesi. This study uses a qualitative descriptive approach with a single case study approach. The results show that Islamic Relief's support is not only limited to material assistance, but also training and mentoring to improve managerial skills and business empowerment. These findings emphasize the importance of a holistic and sustainable approach in ensuring post-disaster economic recovery. Overall, the Islamic Relief Project has made a significant contribution to post-disaster business recovery in the Petobo area, and this approach is expected to be a sustainable and resilient economic recovery strategy for disaster-affected communities.